A Research on Monetary Literacy of Senior Secondary School Teachers: An investigation into the monetary literacy levels of senior secondary school teachers in Varanasi (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The prime motivation behind the paper was to investigatethe status of monetary literacy around the senior secondary school teachers inVaranasi. To figure out the status of monetary literacy of senior secondaryschool teachers the 'Monetary literacy test' created via analyst was managed. Takingcomprehension of the way of sample, 'Accidental sampling procedure' wasutilized. From one perspective sample was Incidental what's more then again itwas purposive as it served the motivation behind the study. U.P. board and CBSEaffiliated schools were recognized for data accumulation. The study found thatteachers, especially senior secondary school teachers, had moderately lowlevels of beginning monetary literacy. The level of Monetary literacy was foundto shift crosswise over sex, school boards, and the past formal economicsdirection.